Success Community College: An Examination of Organizational Change - Levin, John S. (Canadian Journal of Higher Education, 1995)
An examination of organizational change was carried out at a community college where there was evidence of events which might precipitate change, including events such as leadership succession, new management and governance structures, and proposed cultural shifts. The college during a prolonged period experienced considerable growth in personnel, in facilities, and in students. The beginning of this period coincided with presidential succession, and the period itself was accompanied by a sizable turnover of administrative personnel (approximately 60%, or 10 of 16, of educational administrators). These factors provide the conditions for organizational change, certainly to the extent that "change refers to alterations in the allocation of resources, distribution of power, and the internal structure of the organization" (Hasenfeld 1983, p. 219). While change can lead to organizational success, on another level these changes can result in the victimization of organizational members. This case indicates that not all organizational change has a happy ending, and that those who promote and facilitate the change process for community colleges should consider all potential outcomes of change, including the victimization of organizational participants.